2015
DOI: 10.1073/pnas.1518960113
|View full text |Cite
|
Sign up to set email alerts
|

Distal substitutions drive divergent DNA specificity among paralogous transcription factors through subdivision of conformational space

Abstract: Many genomes contain families of paralogs-proteins with divergent function that evolved from a common ancestral gene after a duplication event. To understand how paralogous transcription factors evolve divergent DNA specificities, we examined how the glucocorticoid receptor and its paralogs evolved to bind activating response elements [(+)GREs] and negative glucocorticoid response elements (nGREs). We show that binding to nGREs is a property of the glucocorticoid receptor (GR) DNA-binding domain (DBD) not shar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 46 publications
(56 reference statements)
5
53
0
Order By: Relevance
“…This contrasts strongly with the cooperative binding seen at canonical GBSs 25 . Furthermore, nuclear magnetic resonance (NMR) studies indicate that the D-loop residues display significant changes in chemical environment consistent with dimerization when bound to a canonical GBS, whereas they are unaffected on binding to an IR-GBS 26 . As with canonical GBSs, it has not been examined whether LBD-LBD interactions participate in GR binding to IR-GBSs.…”
Section: Gr-genome Interactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…This contrasts strongly with the cooperative binding seen at canonical GBSs 25 . Furthermore, nuclear magnetic resonance (NMR) studies indicate that the D-loop residues display significant changes in chemical environment consistent with dimerization when bound to a canonical GBS, whereas they are unaffected on binding to an IR-GBS 26 . As with canonical GBSs, it has not been examined whether LBD-LBD interactions participate in GR binding to IR-GBSs.…”
Section: Gr-genome Interactionsmentioning
confidence: 99%
“…Taken together, we infer from these in vitro studies that monomeric GR most likely binds these elements in vivo . Other 3-keto steroid receptors, MR, PR and AR, can all bind to a canonical GBS, but only GR is able to bind an IR-GBS 26 . Even the MR DBD, which shares 90% sequence identity with the GR DBD, cannot bind or repress transcription from an IR-GBS, owing to epistatic mutations that occurred during the evolution of the steroid receptor family that limit this function in all steroid receptors except GR 26 .…”
Section: Gr-genome Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…We explored three independent studies to demonstrate how well Evolusec (both DSO-sec and JTT-sec) captures evolutionary changes of structural traits. The studies targeted an ancient protein kinase (Wilson et al, 2015), an ancient polar amino acid-binding protein (Clifton and Jackson, 2016), and an ancient DNA-binding domain (Hudson et al, 2016); the proteins represent a range of sequence and structural diversity. Ancestral sequences were inferred from the amino acids of modern proteins, synthesised and their three-dimensional structures were determined.…”
Section: Reconstructing Ancestral Secondary Structure From Modern Promentioning
confidence: 99%
“…Zuckerkandl and Pauling's idea of inferring ancestors from modern proteins (Zuckerkandl and Pauling, 1965) has had recent success in decoding the origins and the determinants of complex protein functions (Hochberg and Thornton, 2017). For example, by comparing inferred ancestors to modern proteins, Wilson et al (2015) elucidated binding affinities in protein kinases, Clifton and Jackson (2016) decoded origins of promiscuity in a solute-binding protein family, and Hudson et al (2016) identified historical amino acid substitutions that alter specificity of a DNA-binding domain. Ancestral sequence reconstruction typically requires a phylogenetic tree, multiple modern protein sequences in an alignment, and an evolutionary model that assigns a probability to evolutionary events.…”
Section: Introductionmentioning
confidence: 99%